Symbolic or Substantial: Firms’ Adaptive CSR Compliance Strategies in Developing Institutional Contexts - Yang, Wooyoung; Kim, Jiyeon (European Journal of Sustainable Development, 2025)
This study examines how institutional development and pressure influence corporate social responsibility (CSR) compliance strategies among firms in developing country contexts. The research uses CSR report data from Chinese A-market companies across 31 provinces over nine years to investigate the relationships between institutional development, pressure on CSR compliance, and firms’ strategic responses. The study employs institutional theory to analyze how firms adjust their CSR compliance behaviors as institutional environments evolve. It explores whether companies engage in symbolic compliance (superficial adoption) or substantial compliance (meaningful integration) of CSR practices. Key findings reveal a significant link between institutional development and pressure levels influencing CSR compliance. The combined effect of development and pressure surpasses the influence of pressure alone. Evidence of symbolic and substantial CSR compliance suggests that firms strategically adjust their efforts based on the institutional environment. This research provides valuable insights for policymakers and stakeholders seeking to encourage meaningful CSR practices. Understanding how firms respond to institutional pressures across different development levels can inform the design of more effective regulatory frameworks and drive impactful CSR initiatives in emerging markets. Keywords: CSR, institutional development, institutional pressure, institutional theory, symbolic, substantial